2018
DOI: 10.1007/s00330-018-5663-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass estimation on breast magnetic resonance imaging in breast cancer patients: comparison between psoas muscle area on computer tomography and pectoralis muscle area on MRI

Abstract: • Pectoralis muscle area can be estimated on breast MRI • Total psoas area on CT and pectoralis muscle area on MRI are strongly correlated • Pectoralis muscle area on breast MRI could estimate the skeletal muscle mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Chang et al (3) suggested that axillary imaging warrants consideration of at least axillary level I or II to examine lymphadenopathy. A degraded muscular status may be indicative of a shorter time of progression (34). Because the structure of pectoralis muscles is anatomically well visualized on CBBCT scans, we also incorporated the tumor involvement of this feature into our analyses to study its correlation with LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (3) suggested that axillary imaging warrants consideration of at least axillary level I or II to examine lymphadenopathy. A degraded muscular status may be indicative of a shorter time of progression (34). Because the structure of pectoralis muscles is anatomically well visualized on CBBCT scans, we also incorporated the tumor involvement of this feature into our analyses to study its correlation with LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, MRIs have been used for muscle quality and quantity evaluations of neuromuscular disorders [58][59][60]. Furthermore, an MRI-only assessed sarcopenia is an important prognostic factor in many types of cancer, including breast cancer, head and neck cancer, and colorectal cancer [61][62][63]. However, this method remains in the early stages for studying sarcopenia in chronic liver disease.…”
Section: Mrimentioning
confidence: 99%
“…The difference was initially not significant at 7 then 14 days but diverged over time and was significantly different at 21 days (PO-S 3% vs PO-NS 7%, p=0.016) and 3 months (PO-S 7% vs PO-NS 17%, p=0.016) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Both PG-SGA and HGS did not correlate with sarcopenia in the postoperative period.…”
Section: Postoperative Nutrition Related Outcomesmentioning
confidence: 99%
“…A common complication in oncology patients is a reduction in body stores, including muscle wasting and subcutaneous fat loss [5]. Sarcopenia is defined by progressive and generalised loss of skeletal muscle mass and strength with a risk of adverse outcomes such as physical disability, poor quality of life, and death [6].…”
Section: Introductionmentioning
confidence: 99%